TINDAK TUTUR ILOKUSI DALAM NOVEL RASA KARYA TERE LIYE - Puspita, Amelia; Patriantoro, Patriantoro; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Language is a means of communivation between people one another. The language used will help humans communicate. Language is also found in novels in the form of speech in the form of conversations or dialog between characters. One of the novels that has a lot of speech is the novel Rasa by Tere Liye. Therefore, the researcher wants to know what illocutionary speech is contained in the novel Rasa by Tere Liye. This study adopted descriptive method and qualitative research form. The research data were obtained in the form of words, phrases and sentences of assertive, directive, commissive, expressive, and declarative illocutionary speech acts contained in Tere Liye"™s novel Rasa. The result of this research is 4 types of illocutionary speech acts, namely assertive as much as 50 data which includes stating 23 utterances, proposing 6 utterances, boasting 3 utterances, complaining 4 utterances, expressing opinions 8 utterances, and reporting 5 utterances; directive as much as 65 data includes ordering 19 utterances, commanding 29 utterances, begging 8 utterances, demanding 2 utterances, giving advice 6 utterances, and inviting 1 utterance; commissive as many as 7 data include promising 2 utterances and offering 5 utterances; expressive as many as 35 data include thanking 8 utterances, congratulating 5 utterances, apologizing 3 utterances, praising 10 utterances and accusing 9 utterances. The research plan is the design of a teahing module for novel texts in grade 12 of Senior High School (SMA).